Calagem superficial e aplicação de gesso em sistema plantio direto de longa duração: efeitos no solo e na sucessão milho/crambe/feijão-caupi - Costa, Claudio Hideo Martins da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Brazil has extensive area with acid soils. This areas under no-till system exists the necessity to apply soil acidity correctives materials. In the short term, the effects of superficial liming is restricted to the upper soil layers. The use of phosphogypsum is an alternative to improve the root environment in the subsurface, and can be used in acid soils as a liming supplement. However, it remains unknown how the surface application of limestone and gypsum affects the physical attributes, soil organic matter and non-traditional crops. The experiment was carried out in an experimental area, in the city of Botucatu (SP, Brazil), continuing a research project that has been conducted since 2002, to evaluate the long-term effects of surface application of lime and gypsum on chemical and physical properties, and organic matter, as well as in plant nutrition and yield components and grain yield of corn, crambe and cowpea, in the crop seasons 2010/11 and 2011/12. The experimental design was a randomized block with 4 replications. The plots were as follows: original condition and application of limestone (2.700 + 2.000 + 2.000 kg ha-1), gypsum (2.100 + 2.100 + 2.100 kg ha-1) and limestone + gypsum [(2.700 + 2.100 kg ha-1) + (2.000 + 2.100 kg ha-1) + (2.000 + 2.100 kg ha-1)], applied in October 2002, November 2004 and October 2010. As summer crop was used corn, and in the off season crambe followed by cowpea. The following evaluations were performed: chemical soil attributes at 12 and 24 months after the last application of inputs; physical fractionation of soil organic matter and soil physical attributes at 24 months after the last application of inputs; and yield components and crop yield. The surface application of limestone, with or without gypsum, were effective in reducing soil acidity to a depth of 0.20 m. The Ca2+ and Mg2+ levels in the soil increased in the surface and subsurface with liming. The Ca2+ ...

No Brasil existem extensivas áreas com acidez do solo. Nesta áreas sob sistema plantio direto existe a necessidade de aplicação de materiais corretivos de acidez. Em curto prazo, os desconhecido como a aplicação de calcário e gesso agrícola em superfície afetam os atributos físicos, a matéria orgânica do solo e culturas não tradicionais. Dentro deste enfoque, o trabalho foi desenvolvido na Fazenda Experimental Lageado, pertencente à Faculdade de Ciências Agronômicas - UNESP, Campus de Botucatu (SP), dando continuidade a um projeto de pesquisa que vem sendo conduzido desde 2002, com o objetivo de avaliar a aplicação superficial de calcário e gesso nos atributos químicos, físicos e na matéria orgânica, bem como na nutrição, na produtividade das culturas do milho, crambe e feijão-caupi, nos anos agrícolas 2010/11 e 2011/12. O delineamento experimental utilizado foi em blocos casualizados, com 4 repetições. Os tratamentos foram constituídos por: controle, aplicação de calcário (2.700 + 2.000 + 2.000 kg ha-1), aplicação de gesso (2.100 + 2.100 + 2.100 kg ha-1), e aplicação de calcário + gesso [(2.700 + 2.100 kg ha-1) + (2.000 + 2.100 kg ha-1) + (2.000 + 2.100 kg ha-1)], aplicados em outubro de 2002, novembro de 2004 e outubro de 2010. No verão foi utilizada a cultura do milho, e na entressafra a cultura do crambe seguida do feijão-caupi. Foram realizadas as seguintes avaliações: atributos químicos do solo aos 12 e 24 meses após a última aplicação dos insumos; fracionamento físico da matéria orgânica do solo e ...
Surface liming and gypsum application under a long-term no-till: effects on soil and in succession corn/crambe/cowpea
Keywords: Feijão-de-corda; Solos - Conservação; Solos - Acidez; Solos - Correção; Matéria orgânica; Adubação; Beans